Activation of PPAR-γ prevents TERT-mediated pulmonary vascular remodeling in MCT-induced pulmonary hypertension. Issue 3 (March 2023) - Hussain, Tafseel; Chai, Limin; Wang, Yan; Zhang, Qianqian; Wang, Jian; Shi, Wenhua; Wang, Qingting; Li, Manxiang; Xie, Xinming
Abstract: Background: It has been demonstrated that elevated telomerase reverse transcriptase (TERT) expression or activity is implicated in pulmonary hypertension (PH). In addition, activation of peroxisome-proliferator-activated receptor γ (PPAR-γ) has been found to prevent PH progression. However, the molecular mechanism responsible for the protective effect of PPAR-γ activation on TERT expression in the pathogenesis of PH remains unknown. This study was performed to address these issues. Methods: Intraperitoneal injection of monocrotaline (MCT) was used to establish PH. BIBR1532 was applied to inhibit the activity of telomerase. The right ventricular systolic pressure (RVSP) and histological analysis were used to detect the development of PH. The protein levels of p-Akt, t-Akt, c-Myc and TERT were determined by western blotting. Pharmacological inhibition of TERT by BIBR1532 effectively suppressed RVSP, RVHI and the WT% in MCT-induced PH rats. Results: Pharmacological inhibition of Akt/c-Myc pathway by LY294002 diminished TERT upregulation, RVSP, RVHI and WT% in MCT-PH rats. Activation of PPAR-γ by pioglitazone inhibited p-Akt and c-Myc expressions and further downregulated TERT, thus to reduced RVSP, RVHI and WT% in MCT-treated PH rats. Conclusions: In conclusion, TERT upregulation contributes to PH development in MCT-treated rats. Activation of PPAR-γ prevents pulmonary arterial remodeling through Akt/c-Myc/TERT axis suppression. Graphical abstract: Image 1